A root cap-localized NAC transcription factor controls root halotropic response to salt stress in Arabidopsis - Lulu Zheng; Yongfeng Hu; Tianzhao Yang; Zhen Wang; Daoyuan Wang; Letian Jia; Yuanming Xie; Long Luo; Weicong Qi; Yuanda Lv; Tom Beeckman; Wei Xuan; et al. (Nature Communications, 2024)
Abstract Plants are capable of altering root growth direction to curtail exposure to a saline environment (termed halotropism). The root cap that surrounds root tip meristematic stem cells plays crucial roles in perceiving and responding to environmental stimuli. However, how the root cap mediates root halotropism remains undetermined. Here, we identified a root cap-localized NAC transcription factor, SOMBRERO (SMB), that is required for root halotropism. Its effect on root halotropism is attributable to the establishment of asymmetric auxin distribution in the lateral root cap (LRC) rather than to the alteration of cellular sodium equilibrium or amyloplast statoliths. Furthermore, SMB is essential for basal expression of the auxin influx carrier gene AUX1 in LRC and for auxin redistribution in a spatiotemporally-regulated manner, thereby leading to directional bending of roots away from higher salinity. Our findings uncover an SMB-AUX1-auxin module linking the role of the root cap to the activation of root halotropism.